2011
DOI: 10.1105/tpc.111.086314
|View full text |Cite
|
Sign up to set email alerts
|

Condensin II Alleviates DNA Damage and Is Essential for Tolerance of Boron Overload Stress in Arabidopsis  

Abstract: Although excess boron (B) is known to negatively affect plant growth, its molecular mechanism of toxicity is unknown. We previously isolated two Arabidopsis thaliana mutants, hypersensitive to excess B (heb1-1 and heb2-1). In this study, we found that HEB1 and HEB2 encode the CAP-G2 and CAP-H2 subunits, respectively, of the condensin II protein complex, which functions in the maintenance of chromosome structure. Growth of Arabidopsis seedlings in medium containing excess B induced expression of condensin II su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 50 publications
7
111
1
Order By: Relevance
“…As mentioned earlier, a recent genetic study in A. thaliana has shown that condensin II is likely to be involved in DSB response and repair (Sakamoto et al 2011). A genetic screen for mutants that exhibit hypersensitivity to excess boron identified two mutants (heb1-1 and heb2-1) that turned out to be defective in the genes encoding the CAP-G2 and CAP-H2 subunits of condensin II, respectively.…”
Section: Dna Damage Response and Repairmentioning
confidence: 93%
See 1 more Smart Citation
“…As mentioned earlier, a recent genetic study in A. thaliana has shown that condensin II is likely to be involved in DSB response and repair (Sakamoto et al 2011). A genetic screen for mutants that exhibit hypersensitivity to excess boron identified two mutants (heb1-1 and heb2-1) that turned out to be defective in the genes encoding the CAP-G2 and CAP-H2 subunits of condensin II, respectively.…”
Section: Dna Damage Response and Repairmentioning
confidence: 93%
“…Whereas the A. thaliana genome has a single essential gene (AtCAP-C) encoding SMC4 (Siddiqui et al 2006), it possesses two paralogous genes for SMC2, known as AtCAP-E1 and AtCAP-E2 (Siddiqui et al 2003 +/À E2 À/À plant results in meristem disorganization and fasciation, indicating that SMC2 activity above a certain threshold is required for proper development of A. thaliana. Very recently, a genetic screen for mutants that exhibit hypersensitivity to excess boron has led to the somewhat surprising conclusion that condensin II is nonessential for mitosis and instead plays a role in alleviating DNA damage (Sakamoto et al 2011). Whereas genetic studies have yet to be reported for the genes encoding condensin I-specific subunits, it is anticipated that condensin I is sufficient for mitotic chromosome assembly and segregation in this organism.…”
Section: Arabidopsis Thalianamentioning
confidence: 99%
“…Moreover, the condensin II-specific subunits apparently play less-important roles than the condensin I-specific subunits during the mitotic chromosome cycle in organisms, such as Drosophila (Savvidou et al 2005;Herzog et al 2013), Arabidopsis thaliana (Sakamoto et al 2011), and C. merolae (Fujiwara et al 2013). Consistent with this view, genome-wide screens for genes affecting chromosome condensation in yeasts and Drosophila have identified condensin I and topoisomerase II (Hirano et al 1986;Samejima et al 1993;Goshima et al 2007;Petrova et al 2012), implicating that no more "major" condensation factors remain to be discovered, at least in these organisms.…”
Section: Condensin I Associates With Chromosomes In Prometaphase Andmentioning
confidence: 99%
“…To examine whether the mms21-1 roots had constitutive activation of DNA damage responses, we first measured the expression of the DSB-inducible genes PARP1, BRCA1, and RAD51 by qRT-PCR (Inagaki et al, 2006;Sakamoto et al, 2011). Plants were grown under normal growth conditions, and the transcript levels of all three genes were higher in the mms21-1 roots than in the wild-type plants (Fig.…”
Section: Mms21-1 Mutant Root Tip Cells Have Increased Dsbsmentioning
confidence: 99%